STRATEGI MANAJEMEN KOMUNIKASI MEDIA ONLINE CERDIK INDONESIA DALAM MENGATASI PERSAINGAN ANTARMEDIA ONLINE - Mustikasari, Reni; Zakiah, Kiki; Rantona, Safutra (Program Studi Ilmu Komunikasi Universitas Komputer Indonesia, 2021)
This Study is purposed to determine how the management communication business strategy which has done by Cerdik Indonesia to overcome the competition between online media. The method which is use in this study is by a qualitative approach with POAC communication management analysis theory. Data collection techniques used in this study are documentation study, literature study, observation and in – depth interviews. The results of this study indicate that the management strategy which is use by Cerdik Indonesia has a good foundation and effective communication. Starting from the planning stage to controlling, the editor- in –chief of Cerdik Indonesia has a full responsibility to compete with online media competitor.